A novel Toxoplasma gondii TGGT1_316290 mRNA-LNP vaccine elicits protective immune response against toxoplasmosis in mice - Li, Dan; Zhang, Yizhuo; Li, Shiyu; Zheng, Bin (Frontiers in Microbiology, 2023)
Toxoplasma gondii (T. gondii) can infect almost all warm-blooded animals and is a major threat to global public health. Currently, there is no effective drug or vaccine for T. gondii. In this study, bioinformatics analysis on B and T cell epitopes revealed that TGGT1_316290 (TG290) had superior effects compared with the surface antigen 1 (SAG1). TG290 mRNA-LNP was constructed through the Lipid Nanoparticle (LNP) technology and intramuscularly injected into the BALB/c mice, and its immunogenicity and efficacy were explored. Analysis of antibodies, cytokines (IFN-γ, IL-12, IL-4, IL-10), lymphocytes proliferation, cytotoxic T lymphocyte activity, dendritic cell (DC) maturation, as well as CD4+ and CD8+ T lymphocytes revealed that TG290 mRNA-LNP induced humoral and cellular immune responses in vaccinated mice. Furthermore, T-Box 21 (T-bet), nuclear factor kappa B (NF-kB) p65, and interferon regulatory factor 8 (IRF8) subunit were over-expressed in the TG290 mRNA-LNP-immunized group. The survival time of mice injected with TG290 mRNA-LNP was significantly longer (18.7 ± 3 days) compared with the survival of mice of the control groups (p＜0.0001). In addition, adoptive immunization using 300 μl serum and lymphocytes (5*107) of mice immunized with TG290 mRNA-LNP significantly prolonged the survival time of these mice. This study demonstrates that TG290 mRNA-LNP induces specific immune response against T. gondii and may be a potential toxoplasmosis vaccine candidate for this infection.